Beyond futebol and language: what have we missed from not paying Brazilian constitutionalism its due attention? Reflections from Chile - Contreras, Pablo; Lovera, Domingo (Revista de Investigações Constitucionais, 2018)
This essay proposes a critical and comparative reflection focusing on the lack of ‘constitutional dialogue’ Chile has developed with Brazil – and vice versa. After proposing a couple of contentions to explain this lack of attention (cultural and constitutional colonialism, on the one hand, coupled with Brazil geopolitical power, on the other), it moves on to lament what this lack of attention has deprived Chile from. As it discusses the means to overcome the lack of legitimacy that affects Chile’s constitutional text, it calls attention to some of the reasons that may explain, and actually justify, the celebratory tone the Brazilian Constitution’s 30th anniversary has acquired.